IERs in reverse supply chain: Be worth lowering or not. (September 2017) - Gu, Qiaolun; Gao, Tiegang
Highlights: The problem that whether the IERs in reverse supply chain is worth lowering or not is studied. A system dynamics model of reverse supply chain with IERs and strategies is developed. A method of optimizing IERs and growth rates of mean profits is presented. The typical strategies with expected growth rates of mean profits are investigated. Sensitivity analysis is performed. Abstract: Inspection-error-rates (IERs) in reverse supply chain have been considered by some researchers. Most of the existing studies assume that the IERs are fixed values. However, the further research efforts on lowering the IERs are rare. Whether the IERs are worth lowering or not? In this paper, this problem is investigated by system dynamics methodology. A system dynamics model of the reverse supply chain with IERs and strategies is developed. Based on the current state of reverse supply chain with IERs which has been operating for many years, three strategies and corresponding expected growth rates of mean profits are designed. A method of optimizing IERs and growth rates of mean profits is presented. By running the model under different situations (what-if), changes of the member's profits with strategies and in current state are simulated. Furthermore, the optimized IERs and growth rates of mean profits of the members are presented via the proposed method and depth analysis. These optimal results can help the collector and the remanufacturer make their decisions.